PENERAPAN MODEL PEMBELAJARAN KOOPERATIF GQGA (GIVING QUESTION AND GETTING ANSWER) BERBANTUAN MEDIA COUPLE CARD UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STOIKIOMETRI - Silvi Ramadhani; Rasmiwetti Rasmiwetti; Maria Erna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research about the GQGA (Giving Question and Getting Answer), model has been conducted in SMAN 4 Pekanbaru. The purpose of this research is to determine wheterthe application of GQGA learning can improve achievement and the influence of application of GQGA learning model in class X IPA SMAN 4 Pekanbaru on the subject improve category N-Gain, Research on the application of cooperative learning model GQGA assisted with couple card media has been done to improve student’s achievement on the subject of stoichiometry. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes, X MIPA 1 class as experiment and X MIPA 3 class as control that randomly selected after testing normality and homogeneity. Experiment class was treated with implementing cooperative learning model GQGA Giving Question and Getting Answer assisted with couple card media and the control class was treated conventional method. Analysis of data used t-test. Data of research obtained tcount > ttable (7,9 > 1,67). It means that using cooperative learning model GQGA assisted with couple card media can improve student’s achievement on the subject of stoichiometry in class X of SMAN 4 Pekanbaru. The category improvement of student’s achievement in experiment class was high category (N-Gain =0,84) and in control class was medium category (N-Gain =0,69).Key Words: GQGA (Giving Question and Getting Answer) Student’s Achievement.